Recent progress of electrochemical hydrogen evolution over 1T-MoS2 catalysts - Zhang, Yicen; Wang, Li; Chen, Qian; Cao, Jing; Zhang, Cen (Frontiers in Chemistry, 2022)
Developing efficient and stable non-noble metal catalysts for electrocatalytic hydrogen evolution reaction (HER) is of great significance. MoS2 has become a promising alternative to replace Pt-based electrocatalysts due to its unique layered structure and adjustable electronic property. However, most of the reported 2H-MoS2 materials are stable but the catalytic activity is not very ideal. Therefore, a series of strategies such as phase modulation, element doping, defect engineering and composite modification have been developed to improve the catalytic performance of MoS2 in HER. Among them, phase engineering of 2H-MoS2 to 1T-MoS2 is considered to be the most effective strategy for regulating electronic properties and increasing active sites. Hence, in this mini-review, the common phase modulation strategies, characterization methods and application of 1T-MoS2 in HER were systematically summarized. Besides, some challenges and future directions are also proposed for the design of efficient and stable 1T-MoS2 HER catalysts. We hope this mini-review will be helpful to researchers currently working in or about to enter the field.